2004
DOI: 10.1017/s1461145704004328
|View full text |Cite
|
Sign up to set email alerts
|

REM sleep and cortisol responses to scopolamine during depression and remission in women

Abstract: Baseline electroencephalographic (EEG) sleep and the EEG sleep response to scopolamine were studied in 10 adult female patients with unipolar major depressive disorder. Subjects were studied twice for two consecutive nights while depressed and, again, during remission. On the second night of each two-night session, normal saline or scopolamine (1.5 microg/kg, i.m.) was administered in a randomized, double-blind, cross-over fashion. Nocturnal urinary free cortisol (NUFC) measures also were collected. Compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 68 publications
0
7
0
1
Order By: Relevance
“…However, the strength of association between REM latency and cortisol values in depressed adolescents was diminished during remission, as was noted in a study of adult depressed patients (Rao et al 2004). It is possible that pharmacological or psychosocial interventions might target the regulatory mechanisms of these two physiological systems to different degrees, thus weakening their link at least temporarily.…”
Section: Rao and Poland 610mentioning
confidence: 88%
See 1 more Smart Citation
“…However, the strength of association between REM latency and cortisol values in depressed adolescents was diminished during remission, as was noted in a study of adult depressed patients (Rao et al 2004). It is possible that pharmacological or psychosocial interventions might target the regulatory mechanisms of these two physiological systems to different degrees, thus weakening their link at least temporarily.…”
Section: Rao and Poland 610mentioning
confidence: 88%
“…Numerous investigations also have presented evidence of hypothalamic-pituitary-adrenal (HPA) dysregulation, typically manifested as cortisol hypersecretion, in adult major depression (for reviews, see Stokes and Sikes 1991; Barden 2004). From various adult samples with depression, including cross-sectional comparison of remitted patients with healthy controls (Hauri et al 1974;Poland et al 1997), single-episode cases versus those with recurrent illness (Giles et al 1989;Thase et al 1995) and prospective follow up of individual patients through recovery (Schulz et al 1979;Rush et al 1986;Kupfer et al 1988;Riemann and Burger 1989;Steiger et al 1989;Steiger et al 1991;Buysse et al 1992;Giles et al 1993;Kupfer et al 1993;Lee et al 1993;Thase et al 1994;Jindal et al 2002;Rao et al 2004), there is emerging consensus that EEG sleep disruptions associated with major depressive illness are remarkably stable from episode to recovery. In contrast to the stability of EEG sleep measures, studies examining HPA function highlight the state-related quality of this physiological system in association with depression (Barden 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note here that all AD, but no MCI subjects, were prescribed anticholinergic medication. Previous experience with anticholinergic’s impact on sleep architecture suggests that the AD group should have faster rather than slower RR max [ 32 , 33 ]. Our work highlights the importance in approaching treatment alternatives for MCI and AD snorers through other perspectives, such as upper airway stabilization and nasal breathing facilitation, particularly because of the significant public health concerns associated with AD.…”
Section: Discussionmentioning
confidence: 99%
“…When breathing is diverted from the nose to the mouth, oscillation power respiration peak dissipates [ 4 ]. In addition to organizing neuronal population activity across brain regions to orchestrate complex behaviors affiliated with orofacial sensation [ 33 ], breathing enhances memory retrieval [ 4 ]. This functional property may have been established early in the evolution of cerebral cortical circuitry when olfaction was a dominant sense and likely formed the tight connections between the olfactory cortex, hippocampus, neocortex and forebrain [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…All these data show that REM sleep in healthy subjects plays an important role in adaptation and in prevention of mental (depressive) disorders. Rao et al (2004) found a tendency for baseline EM density to be higher during remission. On the one hand, increased EM density, especially in the first cycle, predicts the recurrence of depression and is a marker of poor response to treatment.…”
Section: Vs Rotenbergmentioning
confidence: 88%